World Investment and Political Risk 2012 - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2013)
Global economic growth estimates for 2012 indicate a continuing fragile recovery. The ongoing sovereign debt crisis and recession in the euro zone, curtailed bank lending and domestic deleveraging, fluctuating but elevated commodity prices, and the ongoing political turmoil in the Middle East and North Africa have slowed the initial rebound that followed the 2008 global financial crisis. This slow progress has had an impact on developing countries, which initially fared well in terms of rebounding growth rates, private capital flows, and foreign direct investment (FDI). This report examines investors' perceptions and risk-mitigation strategies as they navigate today's uncertain economic waters. It finds that investors continue to rank political risk as a key obstacle to investing in developing countries and are increasingly turning toward Political Risk Insurance (PRI) as a risk-mitigation tool. The insurance industry has responded with new products and innovative ways to use existing products as well as substantial capacity to meet the growing demand.